2012
DOI: 10.3389/fendo.2012.00012
|View full text |Cite
|
Sign up to set email alerts
|

Fluvoxamine Attenuated Endoplasmic Reticulum Stress-Induced Leptin Resistance

Abstract: Increasing evidence indicates that endoplasmic reticulum stress (ER stress) is involved in the development of metabolic syndrome. However, pharmacological treatments targeting ER stress are not well understood. In the present study, we found that fluvoxamine, a selective serotonin reuptake inhibitor used for depression, can attenuate ER stress-induced “leptin resistance,” i.e., insensitivity to the anti-obesity hormone leptin. Treatment with tunicamycin, an ER stress-inducing reagent, caused cell death which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Hosoi et al [179] have demonstrated that the inhibitor of serotonin uptake, fluvoxamine, attenuated ER stress-induced leptin resistance, increasing STAT3 phosphorylation, and reducing food consumption in mice. Moreover, it has been shown that also the gaseous transmitter carbon monoxide was able to revert leptin resistance induced by thapsigargin or tunicamycin in human cells [180].…”
Section: Reduction Of Er Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Hosoi et al [179] have demonstrated that the inhibitor of serotonin uptake, fluvoxamine, attenuated ER stress-induced leptin resistance, increasing STAT3 phosphorylation, and reducing food consumption in mice. Moreover, it has been shown that also the gaseous transmitter carbon monoxide was able to revert leptin resistance induced by thapsigargin or tunicamycin in human cells [180].…”
Section: Reduction Of Er Stressmentioning
confidence: 99%
“…Improvement of insulin signaling and glucose homeostasis. Increase in STAT3 phosphorylation [177][178][179][181][182][183][184].…”
Section: Reduction Of Er Stressmentioning
confidence: 99%
“…4-PBA and TUDCA treatment successfully alleviate hypothalamic ER stress and restore leptin responsiveness in high-fat diet-fed mice by reducing food consumption along with body weight ( 65 ). Hosoi et al has reported that fluvoxamine, a selective serotonin reuptake inhibitor prescribed for the treatment of depression, which binds the ER receptor Sigma1, is able to alleviate ER stress and reverse leptin resistance in cells, and to decrease food intake in mice ( 171 ). Recently, flurbiprofen, a non-steroidal anti-inflammatory drug (NSAID), was shown to reduce ER stress, to attenuate leptin resistance and to reduce the body weight of HFD obese mice ( 172 , 173 ).…”
Section: Decreasing Er Stress With Chemical Chaperonesmentioning
confidence: 99%
“…Recent studies have further tested the ability of other clinical compounds in the resolution of ER stress. Fluvoxamine, a selective serotonin reuptake inhibitor primarily used for a number of anxiety and depressive disorders, attenuates ER stress‐induced leptin resistance in neuronal cell lines and mice [102]. Flurbiprofen is a phenylalkanoic acid derivative of non‐steroidal anti‐inflammatory drugs which is prescribed to treat arthritis.…”
Section: Alleviating Er Stress As a Potential Treatment For Leptin Rementioning
confidence: 99%